1998
DOI: 10.1038/sj.onc.1201932
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 physically associates with p53 and stimulates its transcriptional activity

Abstract: Mutations of the BRCA1 tumor suppressor gene are the most commonly detected alterations in familial breast and ovarian cancer. Although BRCA1 is required for normal mouse development, the molecular basis for its tumor suppressive function remains poorly understood. We show here that BRCA1 increases p53-dependent transcription from the p21 WAF1/CIP1 and bax promoters. We also show that BRCA1 and p53 proteins interact both in vitro and in vivo. The interacting regions map, in vitro, to aa 224 ± 500 of BRCA1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
367
1
4

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(392 citation statements)
references
References 22 publications
18
367
1
4
Order By: Relevance
“…The failure of these promoter-BRCA1 constructs to support development indicates that overexpressed, or mis-expressed, BRCA1 blocks development. This result was anticipated, in part, because of studies which demonstrate very low levels of BRCA1 expression in normal cells, and other studies that show cellular growth-arrest or apoptosis in many cell lines which overexpress BRCA1 (Shao et al, 1996;Wilson et al, 1997;Zhang et al, 1998). When we transfected mammary cell lines with BRCA1 cDNAs linked to BRCA1 promoter sequences, we did not observe apoptosis or cellular arrest (T Lane and E Solomon, preliminary observations).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The failure of these promoter-BRCA1 constructs to support development indicates that overexpressed, or mis-expressed, BRCA1 blocks development. This result was anticipated, in part, because of studies which demonstrate very low levels of BRCA1 expression in normal cells, and other studies that show cellular growth-arrest or apoptosis in many cell lines which overexpress BRCA1 (Shao et al, 1996;Wilson et al, 1997;Zhang et al, 1998). When we transfected mammary cell lines with BRCA1 cDNAs linked to BRCA1 promoter sequences, we did not observe apoptosis or cellular arrest (T Lane and E Solomon, preliminary observations).…”
Section: Discussionsupporting
confidence: 50%
“…The process is complicated by cellular senescence or apoptosis in many cells engineered to overexpress the BRCA1 cDNA from heterologous promoters (Aprelikova et al, 1999;Shao et al, 1996;Wilson et al, 1997;Zhang et al, 1998). Since mouse embryos de®cient in Brca1 die early in development, a straightforward assay of function is to analyse human BRCA1 gene replacement vectors for their ability to rescue Brca1-de®cient mouse embryos.…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 has been shown previously to interact with a number of different proteins, including but not limited to ATF1, p53, Myc, STAT1 and the CBP-interacting protein CtIP (Ouchi et al, 1998(Ouchi et al, , 2000Wang et al, 1998;Yu et al, 1998;Zhang et al, 1998;Houvras et al, 2000). However, in a previous study describing the regulation of the cyclin-dependent kinase inhibitor p27 Kip1 by BRCA1, we determined that none of the already identified partners of BRCA1 were involved with this function (Williamson et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…In view of our data demonstrating for the conformation mutant p53D237 ± 239 the loss of and for the DNA contact mutant p53(273H) the defectiveness in recombination inhibition, these helicase interactions could be envisioned to be of functional signi®cance in recombination control. Most interestingly, the hRad51 complex partner BRCA1 interacts with p53 between amino acids 300 ± 393 (Ouchi et al, 1998;Zhang et al, 1998). BRCA1 can be imagined to stabilize functional interactions between p53 and hRad51.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination appears to be essential during the normal development of mammalian organisms, as can be deducted from the embryonic lethal phenotype of both rad51 nullizygotes (Lim and Hasty, 1996;Tsuzuki et al, 1996), and of BRCA17/7 mice, lacking the tumor suppressor BRCA1 (Hakem et al, 1997;Ludwig et al, 1997), a complex partner of Rad51 (Scully et al, 1997). Survival of the embryos in both knockouts can be prolonged by concomitant knockout of p53, indicating genetic interactions between p53 and Rad51, as well as between p53 and BRCA1 in addition to physical interactions described before (StuÈ rzbecher et al, 1996;Ouchi et al, 1998;Zhang et al, 1998). Previous work has demonstrated that p53 inhibits homologous DNA exchanges in mitotically growing cells (WiesmuÈ ller et al, 1996;Bertrand et al, 1997;Mekeel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%